Potato productivity during the growth biostimulator Aminostym usage - Gavrilyuk , A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To calculate the effectiveness of the effect of stagnation of the biological growth stimulator Aminostim on the productivity of potato crops. Methods. Field (sampling of plant material and its analysis). The study of the effectiveness of the frozen biological product was carried out on the basis of the Ukrainian Research Station for Plant Quarantine of the Institute of Plant Protection of NAAS for implementation in 2023—2024, on a natural infectious background and. The additional preparation was sprayed on vegetative plants (30 ml/10 l/1 sq.m.). Aminostim — contains amino acids that are easily digestible for plants (L-α-amino acids) — 134 g/l, nitrogen dioxide — 24 g/l, water-soluble phosphorus — 20 g/l, water-soluble potassium — 20 g/l, auxins — 10 g/l and cytokinins — 0.03 g/l. During the growing season, the first application of the preparation was carried out when the sprouts were compacted in the rows, and the next three times were applied through the skin after 12 days. Results. The use of Aminostim on potato plants during the growing season had a positive effect on their productivity. The yield increase was 0.3 t/ha, which is 14% more than in the control. The number of tubers per bush is 2.7 pieces higher than in the control variant. Stagnation of the stimulant had a positive effect on the fractional composition of the bulbs. There was a change in the number of potato fraction by 7.6%, while the number of vegetable fraction increased by 12.5%. A large number of bulbs of the large fraction was lost without changes (8.8%). Conclusions. The biological stimulant showed dryness similar to Alternaria of potato. The development of the disease in the Knyaginya variety under the stimulant treatment was 47.5%, while in the control it was 59.4%. From an economic point of view, the most promising is the use of the stimulant Aminostim in organic farming and in systems of integrated protection of potatoes against diseases.